CONDITIONS OF THE HOSPICES FORMING IN THE MODERN CITY SPACE (Municipal economy of cities. Series: «Economy science», 2017)
The problem of hospices designing in the conditions of the modern city is considered. The main aspects of the hospices forming are estimated. The main components of the hospices forming are estimated from the point of view of organization of the city environment. They include physiological parameters of the environment, hospices philosophy, social activity of patients and specifics of the hospice work. The synthesis of these components while studying the literature data and global experience in the design of hospices has allowed to identify several characteristic conditions of the hospices forming in the city space. Based on this data the author considers the ways of organization of a comfortable hospice environment through proper location and use of means of design. The basic approaches of hospices designing in the city space have been stated in accordance with the advanced regulations. Keywords: hospice, city space, society, barrier-free environment